Ecuador : Selected Issues and Statistical Annex. (IMF Staff Country Reports; Country Report ;, 2000)
The crisis in the banking sector was one of the major contributing factors that led Ecuador to abandon its own currency and introduce the U.S. dollar as legal tender. However, to illustrate the weak growth performance of the country, it is necessary to examine the structural weaknesses in the labor market, the tax system, and the trade system. These weaknesses resulted in the increase in poverty and inequality. This paper provides a brief summary of recent economic developments and statistical data on economic indices of Ecuador.